Comparison of pre- and post-implantation of Indonesian-made plates in fracture patients: Functional, radiological, biomechanical and chemical analyses - Lisan, Rizal A.; Mahyudin, Ferdiansyah; Mubarok, Fahmi (Narra Sains Indonesia, 2024)
Bone implants are important in the recovery of fractures and degenerative diseases. Although many implants have been marketed, study on Indonesian-made plates is still limited. The aim of this study was to assess the patients’ functional and radiological improvements and biomechanical and chemical changes of Indonesian-made plates used in long bone fractures. retrospective study was conducted at Semen Gresik Hospital, Gresik, Indonesia. This study included adult patients with long bone fractures who had surgeries with Indonesian plates. Functional improvement (assessed using disabilities of arm, shoulder, and hand (DASH) or lower extremity functional scale (LEFS)) and radiological data (assessed using radiographic union score (RUS)) were assessed in week 4 and month 6, 12, and 15 after surgery. Biomechanical changes (hardness and roughness test) and chemical analysis were assessed after 15 months of use. The normality of the data was tested with Shapiro-Wilk while data analysis was conducted using paired Student t-test or Friedman test as appropriate with type of data. Our data indicated that the DASH and LEFS functional scores had significant improvement over the follow-ups indicating functional recovery. RUS scores also improved over time, indicating a good healing process. Hardness tests on post-surgery implants showed a decrease in hardness of 7.3% and an increase of 3.3% in roughness. Chemical analysis showed a reduction in chemical levels in the implant of 7.8%, indicating durability and minimal toxicity. This study highlights that Indonesian implants have been proven safe to use in fractures. Further examinations with a larger sample and a longer duration of monitoring are recommended for stronger validity.